Damage Evolution of Onnagawa Shale by Postmortem Thresholding of X‐Ray Computed Tomography. Issue 11 (2nd November 2021) - Jayawickrama, E. G.; Muto, J.; Sasaki, O.; Nagahama, H.
Abstract: Onnagawa shale samples are deformed through the brittle‐ductile transition by increasing the confining pressure. Brittle deformation is characterized by longitudinal splitting of the sample at 3% axial strain. A distributed conjugate fracture network characterizes the macroscopic deformation in the ductile field with strain hardening. The onset of transition from brittle to ductile deformation is between 4% and 5% axial strain with a single shear plane defined failure. Deformed samples are scanned in a commercially available X‐ray CT machine to investigate the sensitivity of the fracture network to the choice of threshold voxel value. The primary voxel values of the deformed rock are reversed, and their density distribution is approximated by a normal distribution to extract the voxel value density distribution that fabricated the fracture network (residual). Successive thresholding of the residual histogram shows that the generated fracture network is highly sensitive to the choice of threshold. Post peak thresholding of the residual histogram generates voxel volumes of fractures alone and consecutive thresholding shows that the obtained volume segments of the fractures can interpret possible nucleation, growth, and coalescence within the damaged zone. Results further show similarity to previous 4D tomographic strain localization investigations and damage size distributions by acoustic emission studies. Therefore, despite the postmortem nature of the investigation, the new technique opens possibilities to investigate the possible evolution of fracture properties under elevated confining pressures and in the absence of high energy synchrotron facilities. Plain Language Summary: With the advancement in technology, the methods of observing rock deformation have developed over the years from the very basic laboratory acoustic emission (AE) tests to more advanced 4D tomographic tests that require synchrotron facilities. However, not everyone has the ability to access these synchrotron facilities. Therefore, in this study we examine the possibility of visualizing fracture formation from a postmortem analysis. To this end, we first deform the rocks under several confining pressures in a conventional triaxial deformation apparatus and scan the deformed samples in a commercial X‐ray CT scanner. Then, we extract the fractures from the whole rock using certain statistical methods. Thusly obtained fracture network is then segmented by thresholding the gray scale. Finally, by this thresholding technique we show that the fracture formation within the damaged zone can be visualized for rocks with preexisting cracks. The obtained results have shown much similarity to previous AE and 4D tomographic test results. Therefore, through this method one can obtain information on rock deformation under the absence of synchrotron facilities or at the instances where rock deformation is difficult to be performed in synchrotron facilities under very high confining pressures. Key Points: Fracture network extracted by a residual analysis has been calibrated by pycnometer and thickness gauge volume estimations Segments of the fracture network are visualized by post peak thresholding of the residual histogram Fracture network is sensitive to the choice of threshold and provide insights to compute possible fracture evolution within the damaged zone